Non-nutritional determinants of satisfactory growth among infants and pre-school children in low income communities in Ja-Ela Medical Officer of Health area, Sri Lanka - Champa Kumudini Gunathunga; Wasantha Gunathunga; Shyaminda Basnayake; Punya Arunoda (College of Community Physicians of Sri Lanka, 2017)
Background: In Sri Lanka, poor growth of infants and pre-school children is a persistent concern with 14% of them having low weight for height. It has been observed that some infants grow well and develop successfully even in low income set-ups despite many unfavourable circumstances, a phenomenon that has not been studied adequately.   Objective: To describe the non-nutritional determinants of positive growth among infants and pre-school children in low income communities in Sri Lanka.   Methods: An unmatched case control study including a qualitative arm was carried out. Cases were 'well grown' and controls were 'poorly grown' infants and pre-school children in Ja-Ela Medical Officer of Health area, who were recruited from the child welfare clinic and at home. Growth was determined by weight for age using standard procedure. An interviewer-administered questionnaire obtained data from their mothers/caretakers on the potential determinants of growth. Ten of the cases were randomly selected for the qualitative study and their mothers underwent in-depth interviews.   Results: A total of 51 cases and 67 controls were recruited for the study. Their average family income was Rs. 17,700 (SD=4200). Cases and controls did not differ significantly by the mode of delivery, type of pregnancy, order of pregnancy and whether pregnancy was planned or not. The only non-nutritional determinants of positive growth were: whether the child is easy to be fed (OR=3.58; 95% CI: 1.66, 7.72) and corporative with the mother (OR=3.77; 95% CI: 1.05, 13.54). The qualitative study further identified readiness to eat and preference for a wide variety of food as non-nutritional determinants of positive growth, which seemed to be intrinsic characteristics of a child rather than shared features among the siblings in a family.   Conclusions: Intrinsic characteristics of a child such as readiness to eat, cooperating with the mother and preferring a variety of food partly determine good growth. Dynamics of these characteristics need further study.